Synthesis, characterization, controlled release, and antibacterial studies of a novel streptomycin chitosan magnetic nanoantibiotic - Hussein-Al-Ali, Samer Hasan; El Zowalaty, Mohamed Ezzat; Hussein, Mohd. Zobir; Ismail, Maznah; Webster, Thomas Jay (Dove Medical Press, 2014)
This study describes the preparation, characterization, and controlled release of a streptomycin-chitosan-magnetic nanoparticle-based antibiotic in an effort to improve the treatment of bacterial infections. Specifically, chitosan-magnetic nanoparticles were synthesized by an incorporation method and were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, thermogravimetric analysis, and vibrating sample magnetometry. Streptomycin was incorporated into the nanoparticles to form a streptomycin-coated chitosan-magnetic nanoparticle (Strep-CS-MNP) nanocomposite. The release profiles showed an initially fast release, which became slower as time progressed. The percentage of drug released after 350 minutes was around 100%, and the best fit mathematical model for drug release was the pseudo-second order model. The Strep-CS-MNP nanocomposite showed enhanced antibacterial activity against methicillin-resistant Staphylococcus aureus. This study forms a significant basis for further investigation of the Strep-CS-MNP nanocomposite in the treatment of various bacterial infections.